Rancang Bangun Automatic Transfer Switch (ATS) Hybrid Daya PLN Dan PLTS Pada Sistem Hidroponik - Widiasari, Cyntia; Rizky Fachriansyah (Politeknik Caltex Riau, 2023)
Hydroponic system requires continuous circulation of water to grow plants. To prevent the risk of stopping the circulation of this water, another source of electrical energy is used to backup power sources if there is a blackout at PLN. So, in this research Automatic Transfer Switch (ATS) system was designed in Hydroponics to maintain water circulation. In which this ATS has a contractor that two power sources that can flow and cut off electric current, which is also connected to the MK2P Relay as an inverter switch, and the MCB as a component protector. The backup power source is used by PLTS connected to the inverter, where the inverter is supplied by a battery that is charged by solar panels as a backup power source. The results of this design show that the transfer delay from PLN to PLTS for about 1,52 seconds and PLTS to PLN is 5.40 seconds. The delay is caused by TDR delay set for about 5 seconds to connected to PLN. As well as the reliability that results form this system is also balanced and can provide electric voltage u to 100% performance with experiments using different delays such as 1, 2, 3, 4, and 5 seconds for 10 trials which can turn on a maintain water circulation on hydroponics. Keywords: ATS, PLTS, PLN, Hydroponic, Water circulation.